EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS ANDROID DENGAN GAMIFIKASI PADA PEMBELAJARAN TEKS EKSPLANASI DI SMP - Hanifah, Ifah; Suntini, Sun; Anjasmara, Aan (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research is a continuation of the development research that has been carried out previously with the title "Development of Android-based Learning Media with Gamification in Explanatory Text Learning in Grade VII at SMP Negeri 2 Kuningan" which has just reached the product development stage. This research is motivated by the lack of learning outcomes to understand explanatory texts caused by the lack of learning media about understanding explanatory texts. The purpose of this study is to test the effectiveness of the use of android-based learning media with gamification in learning explanatory texts in junior high school. The method used is pre-experimental research with a one-group pretest-posttest design. Some of the instruments used are the instrument of the explication text comprehension test. After an effectiveness test, the results were obtained that android-based learning media with effective gamification was used in learning explanatory texts in junior high school. It can be seen from the results of the calculation that the value of sig. (2-tailed) is 0.001. On the basis of the Decision, if sig. (2-tailed)<0.05, then Ho was rejected and H1 was accepted. So sig. (2-tailed) 0.001<0.05, so that the hypothesis that android-based media with gamification is effectively used in learning explanatory texts in junior high school can be accepted. This means that there is a difference in students' ability to understand explanatory texts before and after using media. Thus, the results of this study contribute to learning to understand explanatory texts in terms of the use of innovative learning media.